Internal corporate sustainability drivers: What evidence from family firms? A literature review and research agenda. (6th September 2018) - Broccardo, Laura; Truant, Elisa; Zicari, Adrian
Abstract: Despite the many studies on corporate sustainability, few have analyzed the specific case of the family business. Family firms have certain characteristics that make them different from nonfamily firms, making it valuable to analyze whether these peculiarities are also reflected in their attitude toward sustainability. Specifically, the determinants of the sustainability concept in family firms are unclear. Given the importance of family businesses in most economies, this paper will contribute to filling this gap, depicting through a literature review the main determinants that can affect the sustainability approach of the family firm. The systematic review was carried out through a documented process to guarantee its replicability. The findings show that drivers do not have a homogenous impact on sustainability initiatives due to the distinctiveness of these types of firms. This review contributes by systematizing the existing literature on such topics, identifying future research avenues, and providing several stimuli for researchers.